From Tin Pan to TASPO - Brereton, Bridget (Express)
Bridget Brereton reviews pan researcher Kim Johnson's book entitled, "From Tin Pan to TASPO: Steelband in Trinidad, 1939-1951", published by the UWI Press. This is a more academic books as it began its life as a UWI doctoral thesis but the writing style is vivid and straightforward. The book celebrates individual achievement and variation in the evolution of the steelband.
Keywords: Steel bands (Music) -- Trinidad and Tobago -- History -- 20th century; Steel drum (Musical instrument) -- Trinidad and Tobago -- History; Steel band music -- Trinidad and Tobago; Trinidad All Steel Percussion Orchestra -- History